2008
DOI: 10.5650/jos.57.269
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Flaxseed Oil Supplementation May Affect Fasting Blood Serum Glucose Management in Human Type 2 Diabetics

Abstract: Type 2 diabetes is characterized partially by elevated fasting blood serum glucose and insulin concentrations and the percentage of hemoglobin as HbA1c. It was hypothesized that each of blood glucose and its co-factors insulin and HbA1c and would show a more favorable profile as the result of flaxseed oil supplementation. Patients were recruited at random from a population pool responding to a recruitment advertisement in the local newspaper and 2 area physicians. Completing the trial were 10 flaxseed oil male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 31 publications
2
35
1
Order By: Relevance
“…Other investigators, however, reported contradictory results for total n-3 PUFA and ALA. No association was found between total n-3 PUFA intake and glucose metabolism (32) , fasting insulin (33) or type 2 diabetes risk (34) . Two clinical trials showed no beneficial effect of ALA in the form of flaxseed oil on insulin response and glycaemic control (35,36) . Other studies suggested a protective effect of ALA against type 2 diabetes risk (37)(38)(39) .…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators, however, reported contradictory results for total n-3 PUFA and ALA. No association was found between total n-3 PUFA intake and glucose metabolism (32) , fasting insulin (33) or type 2 diabetes risk (34) . Two clinical trials showed no beneficial effect of ALA in the form of flaxseed oil on insulin response and glycaemic control (35,36) . Other studies suggested a protective effect of ALA against type 2 diabetes risk (37)(38)(39) .…”
Section: Discussionmentioning
confidence: 99%
“…To further corroborate these findings, a meta-analysis of 28 studies determined that in 70-90% of trials, triglycerides and HDL-C were unchanged due to ingestion of flaxseed or a flaxseed extract (Pan, Yu, Demark-Wahnefried, Franco, and Lin, 2009). Randomized controlled trials have also determined a null effect of ingested flaxseed oil or ALA on glycemic control (Barre, Mizier-Barre, Griscti, and Hafez, 2008;Taylor et al, 2010), on adiponectin levels or lipid levels Harper et al, 2006). Clearly more research is warranted to determine a consensus on the health benefits of flaxseed oil in regard to these risk factors of CVD.…”
Section: Fatty Acidsmentioning
confidence: 98%
“…Research workers could not explain why only the low dose group experienced improvements, while the high dose group did not. Which is investigated further by research publish at journal of oleo science by Barre et al (2008). Flaxseed oil had no impact on fasting blood serum glucose, insulin or HbA1c levels.…”
Section: Flaxseed Oil For Pre-diabeticsmentioning
confidence: 98%
“…Both omega-3 and omega-6 fatty acids are beneficial for improving lipid profiles in healthy individuals and among type 2 diabetic patients: Supplementation with omega-3 fatty acids lowers triglycerides and VLDL-cholesterol. Type-2 diabetes mellitus (T2DM) is known for disruption in fatty acid metabolism leading to dyslipidemia (Barre et al, 2008). In a study published in Journal of American College of Nutrition in Feb 2010.…”
Section: Flaxseed Oil For Type 2 Diabeticsmentioning
confidence: 99%